Show time : the logic and power of violent display - Fujii, Lee Ann (Cornell University Press, 2021)
"Analyzes the political violence in Rwanda alongside mass murder in Bosnia and the lynching of African Americans in the United States during the Jim Crow era to show how violent acts have been 'choreographed' not only to damage and kill victims but also to make an impact on observers, neighbors, and the larger society"--